PENGARUH PEMBIAYAAN MUDHARABAH DAN PEMBIAYAAN MUSYARAKAH TERHADAP TINGKAT PROFITABILITAS PADA PT. BANK SYARIAH INDONESIA (BSI) PERIODE TAHUN 2021-2023 - Nirda; Sulastri (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
Sambas State Polytechnic (Poltesa) is a state vocational higher education institution located in Sambas Regency, West Kalimantan. It was established on August 26, 2011, based on the Regulation of the Minister of National Education of the Republic of Indonesia Number 102 of 2011. Poltesa was founded to meet the demand for vocational higher education in the Indonesia–Malaysia border area, particularly in Sambas and its surrounding regions. With a focus on practice-based education at the diploma (D-III) and applied bachelor's (D-IV) levels, Poltesa is committed to producing graduates who are job-ready and aligned with local potential. In addition, the campus actively engages in community empowerment, applied research, and vocational training targeting MSMEs, farmers, fishers, and other local economic actors, thereby supporting sustainable development in underdeveloped, frontier, and outermost (3T) regions. This study aims to determine whether there is a positive and significant influence of customer interest on financing mutation decisions using the mudharabah contract at BSI Sambas Branch. This research uses a quantitative method with a causal associative approach. The total population in this study was 172 people, and the sample size was determined using Roscoe’s theory, resulting in 20 respondents. The type of data used is primary data obtained from questionnaires. The data were analyzed using normality tests, heteroscedasticity tests, autocorrelation tests, simple linear regression analysis, and hypothesis testing using SPSS 23. The results of the study indicate that there is a positive and significant influence of customer interest on financing mutation decisions with the mudharabah contract at BSI Sambas Branch, as evidenced by a t-value of 0.678 and a significance value of 0.000 < 0.05. Furthermore, the Adjusted R Square value was 0.48. Thus, it can be concluded that customer interest influences financing mutation decisions at Sambas State Polytechnic by 48%, while the remaining 52% is influenced by other variables not included in this study.